A importância da prática do registro reflexivo na formação do professor da Educação Infantil - Servilha, Thaionara (2024)
This study aims to understand the importance of recording in reflecting on the practice of Early Childhood Education teachers, in an action research process, discussing how this type of writing can contribute to the construction of pedagogical authorship. The theoretical-methodological framework was based on the principles of action-research (EBBUTT and ELLIOT, 1990; THIOLLENT, 2011; TRIPP, 2005) and studies on the continued training of in-service teachers (TARDIFF, 2000; PLACCO, 2012; FREIRE, 1996), and the reflective record (HOYUELOS and RIERA, 2019; ZABALZA, 2004; FORMOSINHO and PASCAL (2019), MELLO, BARBOSA and FARIA (2020) and PROENÇA (2018, 2022). Six teachers who have been teaching for at least five years in Early Childhood Education. The methodological procedures for data production were: semi-structured interviews, reflective meetings and prose analysis. The interviews were carried out individually, using the Microsoft Teams platform. The five reflective meetings helped the group to find creative and diversified approaches to understand the practice of recording as a fundamental axis of monitoring children and evaluating their own practice in a meaningful way. Analysis of the results indicates that the action research was successful, as it enabled positive changes in the practice of the participating teachers, which they started with uniform writing to then compose a narrative that values the children's uniqueness and choices. It is understood that these changes can be assimilated as indicators of the process of constructing the teachers' authorial writing, perceived and developed during the action research